The impact of fiscal policy and inflation on national saving. A reply - MODIGLIANI, F.; JAPPELLI, T.; PAGANO, M. (PSL Quarterly Review, 2013)
The article serves as a response to Nicola Rossi’s critique of the authors’ previous work on fiscal policy and national savings in Italy. The authors reaffirm their previous finding that deficits have indeed reduced national savings and in particular make two points. First, contrary to his assertions, Rossi’s evidence is inconsistent with the Ricardian Equivalence Proposition. Second, this failure becomes even more apparent if one relies on the updated formulation and improved data underlying the more recent contribution of Modigliani and Jappelli (1987). JEL: E31, E62